Diet supplemented with olive cake as a model of circular economy: Metabolic and endocrine responses of beef cattle - Bionda, Arianna; Lopreiato, Vincenzo; Crepaldi, Paola; Chiofalo, Vincenzo; Fazio, Esterina; Oteri, Marianna; Amato, Annalisa; Liotta, Luigi (Frontiers in Sustainable Food Systems, 2022)
Introduction Integrating by-products into livestock diet represents a great opportunity for implementing the concept of circular economy while reducing feed costs. Olive cake (OC) is considered an agro-industrial waste, but the high content of valuable metabolites makes it a promising feed integration. Therefore, this study investigated the effect of OC integration in beef cattle diet on different blood parameters. Methods Forty-eight young growing fattening Limousines-−24 bulls (body weight 350 ± 15 kg) and 24 heifers (280 ± 10 kg)—, aged 240 ± 20 days, were randomly allocated to 1 of 3 dietary treatments: concentrate at 0% (Control group: CTR), 10% (Low-olive cake group: L-OC), or 15% (High-olive cake group: H-OC) of OC inclusion. Blood samples and body weights were collected before administrating the supplemented diet (0 d), at the end of the stocker growing phase (56 d), and at the end of the fattening (147 d). After being slaughtered, animal carcasses were weighted. A linear regression model was fitted for each blood parameter with the 0 d as covariate and diet, time, sex, diet × time, and diet × sex as fixed effects. Results In males, body weight was highest in CTR, but carcass weight was similar in all the groups. All the blood parameters were within physiological ranges, independently from the animal diet. CTR group showed the highest alanine aminotransferase (ALT, P = 0.0027) and creatine kinase (P = 0.0119), whereas total bilirubin (P = 0.0023) was higher in H-OC than in CTR. Moreover, ALT was highest in CTR at 56 d, becoming similar in all the groups at 147 d (P = 0.0280). Instead, the increase observed in total cholesterol from 56 to 147 d was lower in H-OC compared with CTR and L-OC (P = 0.0451). A significant effect of diet × sex interaction was observed on triglycerides, urea, liver enzymes, and insulin. These data support the OC inclusion of up to 15% of the concentrate with no detrimental effect on beef cattle metabolic status. Discussion In conclusion, OC can be considered as a component in beef diet giving an opportunity to improve agriculture sustainability.